MENGUJI NETRALITAS ILMU PENGETAHUAN - SAIFULLAH SAIFULLAH (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2021)
The polemic in the discussion of women's domestic and public roles is the inaccurate interpretation of gender in the perspective of social, economic, legal, political and religious construction. As a result, one of the sexes is marginalized and subordinated. Women and men are not placed as human beings who have equal opportunities. The error in interpreting the two roles of the human type is called gender bias. It is a must to carry out reinterpretation so that there is a shared awareness that there are equal opportunities and treatment in carrying out their duties as servants of God.